Analisis Kebijakan KUA Medan Kota dalam Penanganan dan Pencegahan Pernikahan Dini - Heru Syahputra; Maulana Bagas Perkasa; Adek Trie Maylani; Muhammad Rizky Gurning; Muhammad Aziz Ramadhana (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Early marriage is a complex social issue that requires special attention due to its negative impacts on individual development, health, and family stability. In Indonesia, policies related to early marriage are regulated in Law No. 16 of 2019, which sets the minimum age for marriage. The Office of Religious Affairs (KUA) Medan City plays a crucial role in addressing and preventing early marriage through various policies and programs, one of which is youth counseling and the certificate of marriage eligibility program. This study aims to analyze KUA Medan City's policies on handling and preventing early marriage and to assess the effectiveness of these programs. The research was conducted using a qualitative approach through an internship at KUA Medan City, involving observation and interviews with relevant stakeholders. The findings show that KUA Medan City has implemented policies to address early marriage effectively, although there are several challenges in its implementation, such as a lack of public understanding regarding the legal marriage age and low interest in participating in marriage counseling programs. In conclusion, while significant efforts have been made, there is still a need to raise public awareness and expand access to services provided by KUA to reduce the incidence of early marriage in the area.